Effects of a relined fiberglass post with conventional and self-adhesive resin cement - Wilton Lima dos Santos Junior; Marina Rodrigues Santi; Rodrigo Barros Esteves Lins; Luís Roberto Marcondes Martins (Restorative Dentistry & Endodontics, 2024)
ObjectivesThis study was conducted to evaluate the mechanical properties of relined and non-relined fiberglass posts when cemented to root canal dentin using a conventional dual-cure resin cement or a self-adhesive resin cement.Materials and MethodsTwo types of resin cements were utilized: conventional and self-adhesive. Additionally, 2 cementation protocols were employed, involving relined and non-relined fiberglass posts. In total, 72 bovine incisors were cemented and subjected to push-out bond strength testing (n = 10) followed by failure mode analysis. The cross-sectional microhardness (n = 5) was assessed along the root canal, and interface analyses (n = 3) were conducted using scanning electron microscopy (SEM). Data from the push-out bond strength and cross-sectional microhardness tests were analyzed via 3-way analysis of variance and the Bonferroni post-hoc test (α = 0.05).ResultsFor non-relined fiberglass posts, conventional resin cement exhibited higher push-out bond strength than self-adhesive cement. Relined fiberglass posts yielded comparable results between the resin cements. Type II failure was the most common failure mode for both resin cements, regardless of cementation protocol. The use of relined fiberglass posts improved the cross-sectional microhardness values for both cements. SEM images revealed voids and bubbles in the incisors with non-relined fiberglass posts.ConclusionsMechanical properties were impacted by the cementation protocol. Relined fiberglass posts presented the highest push-out bond strength and cross-sectional microhardness values, regardless of the resin cement used (conventional dual-cure or self-adhesive). Conversely, for non-relined fiberglass posts, the conventional dual-cure resin cement yielded superior results to the self-adhesive resin cement.